The experiential learning cycle and its application towards the transformation of governmental extension services in sub-Saharan Africa - Percy, Rachel [Verfasser] (My University, 1999)
"This article focuses on the use of the experiential learning cycle in the training of staff within the governmental extension services of sub-Saharan Africa. It starts with reference to a project in Ethiopia in which the experiential learning cycle was employed in a sequential training of trainers within the Extension Division of the Ministry of Agriculture. The project involved the use of participatory approaches and gender analysis in ensuring that the extension services became more client-oriented with particular reference to women. The project objectives, training process and the complementarity between the use of participatory rural appraisal (PRA) and the experiential learning cycle are examined. Outcomes of the project in relation to experiential learning, as well as the enabling and constraining factors to the process, are reviewed. From this specific case, a more general analysis is drawn concerning the changing role of the extension worker and the consequent changes needed in both content and style of change agent training. It is suggested that experiential learning forms the basis of new extension approaches being taken up world-wide such as participatory technology development and farmer-based extension. The decentralization of extension services which is becoming more and more an issue in sub-Saharan Africa provides an opportunity for farmers to take 'centre-stage' and for farmers, agricultural research and extension to work together in partnership. The congruence between experiential learning and participatory approaches involved in this partnership can contribute to the transformation of 'top-down' extension services to those supporting sustainable and farmer based development." (Authors' abstract, BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; I 2.3.1 Afrika; Erwachsenenbildung; Erfahrungsorientiertes Lernen; Berufliche Weiterbildung; Subsahara-Afrika